Periods of weed interference in chickpea grown under different doses of nitrogen fertilizer topdressing (Acta Scientiarum. Agronomy, 2018)
Weed interference can reduce chickpea growth and, therefore, productivity depending on the period of coexistence and the nutritional status of the crop, among other factors. A study was performed over two crop years to estimate the critical period of weed interference (CPWI) during chickpea production under three doses of nitrogen (N) fertilizer topdressing (0, 50, and 75 kg N ha-1). The experiments were conducted at 0, 7, 14, 21, 28, 35, 42, 56, 63, and 140 days after emergence (DAE) of chickpea/weed coexistence under two conditions: initially weed-free and initially weed-infested. The presence of weeds negatively affected chickpea production and reduced yields by 70% on average regardless of N rate, rendering the crop economically unfeasible. The CPWI ranged from 5 to 76 DAE and was not affected by N topdressing up to 75 kg N ha-1 in both crop years, assuming an acceptable production loss of 5%. Although the CPWI without fertilization (0 kg N ha-1) was similar to that when fertilized with 50 and 75 kg N ha-1, the two topdressing doses increased chickpea productivity by 37% and 51%, on average, respectively.